SHB1/HY1 Alleviates Excess Boron Stress by Increasing BOR4 Expression Level and Maintaining Boron Homeostasis in Arabidopsis Roots - Lv, Qiang; Wang, Lei; Wang, Jin-Zheng; Li, Peng; Chen, Yu-Li; Du, Jing; He, Yi-Kun; Bao, Fang (Frontiers in Plant Science, 2017)
Boron is an essential mineral nutrient for higher plant growth and development. However, excessive amounts of boron can be toxic. Here, we report on the characterization of an Arabidopsis mutant, shb1 (sensitive to high-level of boron 1), which exhibits hypersensitivity to excessive boron in roots. Positional cloning demonstrated that the shb1 mutant bears a point mutation in a gene encoding a heme oxygenase 1 (HO1) corresponding to the HY1 gene involved in photomorphogenesis. The transcription level of the SHB1/HY1 gene in roots is up-regulated under excessive boron stimulation. Either overexpressing SHB1/HY1 or applying the HO1 inducer hematin reduces boron accumulation in roots and confers high boron tolerance. Furthermore, carbon monoxide and bilirubin, catalytic products of HO1, partially rescue the boron toxicity-induced inhibition of primary root growth in shb1. Additionally, the mRNA level of BOR4, a boron efflux transporter, is reduced in shb1 roots with high levels of boron supplementation, and hematin cannot relieve the boron toxicity-induced root inhibition in bor4 mutants. Taken together, our study reveals that HO1 acts via its catalytic by-products to promote tolerance of excessive boron by up-regulating the transcription of the BOR4 gene and therefore promoting the exclusion of excessive boron in root cells.